2012
DOI: 10.1001/archophthalmol.2012.215
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Retinopathy of Prematurity Using the Screening Algorithm WINROP in a Mexican Population of Preterm Infants

Abstract: In this Mexican population of preterm infants, WINROP detected type 1 ROP early in 84.7% of very preterm infants and correctly identified 26.6% of infants who did not develop type 1 ROP. Uncertainties in dating of pregnancies and differences in postnatal conditions may be factors explaining the different outcomes of WINROP in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 20 publications
4
65
2
2
Order By: Relevance
“…The other factor contributing to the different WinROP outcomes may lie in differences in the quality of care for prematurely born neonates in Europe and the USA compared to countries where such care may not be so readily available. The importance of this factor is supported by the fact that in our study (as well as in the studies from Sweden or USA), practically no neonates born after GW 29 developed serious ROP that would require treatment 26,32,33,[38][39] while multiple cases requiring treatment were reported in the studies from Brazil, Mexico or China [35][36][37] . In attempts to use the WinROP system for predicting development of ROP (type 1 -3), all test characteristics decreased significantly.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The other factor contributing to the different WinROP outcomes may lie in differences in the quality of care for prematurely born neonates in Europe and the USA compared to countries where such care may not be so readily available. The importance of this factor is supported by the fact that in our study (as well as in the studies from Sweden or USA), practically no neonates born after GW 29 developed serious ROP that would require treatment 26,32,33,[38][39] while multiple cases requiring treatment were reported in the studies from Brazil, Mexico or China [35][36][37] . In attempts to use the WinROP system for predicting development of ROP (type 1 -3), all test characteristics decreased significantly.…”
Section: Discussionsupporting
confidence: 76%
“…So far, our results are in accordance with the results from Sweden and USA reporting 100% sensitivity (and therefore, by induction, 100% negative predictive values) (ref. 26,32,33,[38][39] ) while studies from China, Mexico, Brazil or Korea [34][35][36][37] reported sensitivity values ranging from 85% to 95%. The WinROP system correctly identified all 24 infants requiring or potentially requiring treatment (Type 1 or Type 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A web‐based prediction tool–weight, insulin‐like growth factor 1, neonatal, retinopathy of prematurity (WINROP) – based on weight development, predicts ROP needing treatment with high sensitivity in settings with highly developed neonatal care 7, 8, but with lower sensitivity in settings with poor oxygen control 9.…”
Section: Introductionmentioning
confidence: 99%
“…Its variable specificity and poor positive predictive value in studies (table) 98,100,[121][122][123][124][125][126] suggest that the algorithm should be used in addition to conventional screening guidelines. WINROP does not currently include infants with a gestational age at birth of more than 32 weeks.…”
Section: Classification and Screeningmentioning
confidence: 99%